PEMETAAN PERSEPSI MEREK HANDPHONE BLACKBERRY, NOKIA, SAMSUNG, DAN IPHONE DI KALANGAN MAHASISWA UNIVERSITAS RIAU - Denny Julio; Zulkarnain '; Henny Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research means to map collegers' perceptions of brand handphone, which handphone brand is Blackberry, Nokia, Samsung, and iPhone. In this research, researchers used a variable of product attributes, there are product design, product specifications, product pricing, product warranties, and image quality. This research used a non-probability sampling, is the purposive sampling. The number of samples in this research a total of 120 samples were obtained from the theory of Roscoe. This research uses an analytical tool in the form of correspondence analysis and analysis of preferences, which is processed with SPSS version 20. From the analysis of the correspondence there are three perceptual maps, each of which illustrates a comparison of brands, comparison of attributes, and the comparison brand and attribute the Cartesian diagram. Further analysis of preference to see the most superior brands of handphones on each attribute.Keywords: perceptual map, attribute product, correspondence analysis